PENGEMBANGAN MEDIA PEMBELAJARAN KARTU DOMINO SISTEM PERNAPASAN MANUSIA (DOSINAS) PADA MATA PELAJARAN IPAS SISWA KELAS V SD NEGERI 41 KOTA LUBUKLINGGAU - Ria Kurnia; Yuni Krisnawati; Tidi Maharani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to produce a learning media for the human respiratory system (dosinas) domino card. This type of research is Research and Development (RnD) with a 4D development model. The subjects of this study were fifth grade students of SD Negeri 41 Lubuklinggau. Data collection techniques used validity questionnaires and tests. Based on the results of the validation of the domino card learning media from media experts, language experts, and material experts, it shows that the human respiratory system (dosinas) domino card learning media meets the valid criteria with an average score of 0.92. Meanwhile, from the analysis of teacher and student practicality, it was found that the human respiratory system (dosinas) domino card learning media met the practical criteria with an average score of 89.33%. In the effectiveness test, the N-gain (g) was obtained at 0.73 with a high classification and the assessment of student learning activities obtained an average percentage of 88.90% with very active criteria. Based on the research results, it can be concluded that the human respiratory system domino card learning media (dosinas) has been proven valid, practical, and effective for use in the science subject of the human respiratory system in elementary schools.